Physicochemical and thermal properties of taro (Colocasia esculenta sp) powders as affected by state of maturity and drying method - Himeda, M. (Springer India, 2012)
The study was aimed at determining the effect of harvesting time and drying method on the thermal and physicochemical properties of taro powder, Sosso ecotype. A 5 × 2 factorial experiment with 5 harvesting times (6, 7, 8, 9 and 10 months after planting) and 2 drying methods (sun and electric oven drying) was used for this purpose. The variance component analysis revealed harvesting time as the most important factor affecting all the variables measured. In particular the proteins and available sugar contents of the powders increased significantly with increase in harvesting time. The same was true of the gelling property and water absorption capacity of the powders. It was equally observed that the temperatures (start, peak and end) and enthalpy of gelatinization of the powders increased with harvesting time. It is concluded that harvesting sosso-taro at full maturity (10 months after planting) and sun-drying produces food powders with excellent gelling properties among others.